INTERNALIZATION OF ISLAMIC CHARACTER EDUCATION VALUES IN THE NOVEL ANAK KUAT BY TERE LIYE - Wida, Sholehatul; Hifdil Islam, Muhammad; Herwati (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This research is intended to explore and interpret the values of Islamic character education implied in the novel Anak Kuat by Tere Liye. This research is motivated by the decline of morals in the field of education as well as in the general public. Therefore, the role of education, especially character education, is very much needed to be constantly taught and instilled in social life. The novel titled Anak Kuat was chosen because it is one form of literary work that contains many moral messages and Islamic values that can shape the reader's character into a resilient and ethical individual. This study is a literature-based research (Library Research) that employs a descriptive qualitative approach as its analysis method. The object of study in this research is the novel Anak Kuat by Tere Liye, which tells the story of a child's struggle in facing various challenges, both physically and emotionally. This novel contains important character values such as honesty, hard work, independence, responsibility, and social concern, which are implicitly depicted through the journey of the main character in living their life, identified through the narration and dialogues between characters that reflect Islamic teachings in a contextual, applicable, and relevant manner to the realities of contemporary life, especially in shaping the character of the younger generation.